Clinical application of 18F‐fluoro‐2‐deoxy‐D‐glucose positron emission tomography/computed tomography in breast cancer. (24th November 2013) - Bernsdorf, M.; Graff, J.
Summary Positron emission tomography (PET)/computed tomography (CT) is not suited for primary diagnostics of breast tumours and it cannot replace sentinel lymph node technique in determining metastases to the axilla. PET/CT has a high sensitivity and specificity regarding the detection of loco‐regional recurrence and metastases to mediastinal and internal mammary lymph nodes, as well as distant metastases. Whether the method can replace conventional methods, or be a supplement when this is non‐conclusive, remains unresolved. PET/CT cannot be recommended for routine follow‐up but is recommended in patients with suspected relapse when conventional imaging has given equivocal results. PET/CT can be applied to confirm isolated loco‐regional relapse or metastatic lesion detected by conventional imaging. PET/CT has a high sensitivity for detecting response to treatment, but a low specificity calls for cautions. Further investigations into the use of PET/CT to predict and monitor response are warranted, before this approach may find its way into a clinical setting. In the future, PET/CT will probably find increasing use in treatment planning and evaluation of patients with breast cancer.